2006
DOI: 10.1038/nature05320
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical evolution of ecosystems

Abstract: The assembly of an ecosystem such as a tropical forest depends crucially on the species interaction network, and the deduction of its rules is a formidably complex problem. In spite of this, many recent studies using Hubbell's neutral theory of biodiversity and biogeography have demonstrated that the resulting emergent macroscopic behaviour of the ecosystem at or near a stationary state shows a surprising simplicity reminiscent of many physical systems. Indeed the symmetry postulate, that the effective birth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 129 publications
(164 citation statements)
references
References 26 publications
7
154
2
1
Order By: Relevance
“…Different works have recently analyzed this type of models, showing that time-dependent habitat preference greatly improves predictions of empirical ecological patterns with respect to purely neutral theories [31,[85][86][87]. In particular, it has been claimed that these models provides more realistic estimates of dynamical quantities, such as average species persistence times and distributions of species turnover [88], compared with their neutral counterparts.…”
Section: E Temporally-dependent Habitat Preferencesmentioning
confidence: 99%
“…Different works have recently analyzed this type of models, showing that time-dependent habitat preference greatly improves predictions of empirical ecological patterns with respect to purely neutral theories [31,[85][86][87]. In particular, it has been claimed that these models provides more realistic estimates of dynamical quantities, such as average species persistence times and distributions of species turnover [88], compared with their neutral counterparts.…”
Section: E Temporally-dependent Habitat Preferencesmentioning
confidence: 99%
“…To make more powerful inferences from neutral theory, an important step will be to exploit this ability and combine fitting of species abundances with temporal dynamics of abundance [21,22], SARs [23,24], or phylogenetic data [25]. It is sometimes found that the classic neutral model fails to match patterns; for example, spatially explicit patterns.…”
Section: Reviewmentioning
confidence: 99%
“…The characterization of biodiversity similarity among different LCs of the river network is carried out within a stochastic ecological framework (25)(26)(27)(28)(29) that allows us to formulate an analytically tractable model. We focus mainly on the study of a random variable, J(d), the relative fraction of common species between 2 LCs at distance d ϭ 0, 1, 2, … in link units.…”
Section: Modeling Spatial Biodiversity Similaritymentioning
confidence: 99%